Comparison of rumen contents’ characteristics in Nguni and Bonsmara cows raised under two different grazing systems (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aimed to evaluate rumen fermentation parameters influenced by both grazing system and breed.Materials and Methods: A 2 × 2 factorial design was employed, involving 40 cows with matched age, parity, and physiological status. The cows were evenly divided between Bonsmara and Nguni breeds, as well as communal and commercial grazing systems. Rumen fluid samples were collected and analyzed for parameters including ammonia-nitrogen (NH3-N), pH, temperature, and volatile fatty acids (VFAs).Results: Nguni cows exhibited significantly higher ruminal NH3-N levels (p < 0.05) compared to Bonsmara, ranging from 69.05 to 96.78 mg/l. Commercial grazing demonstrated significantly higher NH3-N concentrations (p < 0.05) than communal grazing. Ruminal pH, temperature, total VFAs, and specific VFAs (Iso-butyrate, valeric, and iso-valeric) did not show significant differences (p > 0.05). However, total VFAs were slightly lower in communal grazing (78.87 mmol/l) than in commercial grazing (89.80 mmol/l). Acetate, propionate, butyrate, and the acetate to propionate ratio did not display significant differences (p > 0.05) between breeds but varied between grazing systems. Communal systems had higher acetate and acetate to propionate ratio (p < 0.05), while commercial systems showed higher propionate and butyrate levels (p < 0.05).Conclusion: Grazing conditions significantly influenced rumen fermentation parameters, irrespective of breed. Further research is necessary to explore the relationship between forage conditions, diversity, and rumen fermentation within different grazing systems.Adv. Vet. Anim. Res., 11(2): 349-355, June 2024http://doi.org/10.5455/javar.2024.k783